A New Monoacylglycerol from the Fruiting Bodies of Gymnopilus Spectabilis. (March 2016) - Suh, Won Se; Lee, Seoung Rak; Kim, Chung Sub; Moon, Eunjung; Kim, Sun Yeou; Choi, Sang Un; Kang, Ki Sung; Lee, Kang Ro; Kim, Ki Hyun
Bioassay-guided fractionation and chemical investigation of the MeOH extract of the wild mushroom Gymnopilus spectabilis resulted in the isolation of a new monoacylglycerol, together with five known compounds. The structure of the new compound (2′ S ) −1- O -(6, 6-dimethoxyhexanol)-glycerol was elucidated on the basis of 1D and 2D NMR ( 1 H and 13 C NMR, 1 H- 1 H COSY, HMQC and HMBC) spectroscopic data as well as chemical reactions. The known compounds were identified by comparison of their spectroscopic and physical data with the reported values. The metabolites were evaluated for their anti-proliferative activities against four human tumour cell lines (A549, SK-OV-3, SK-MEL-2 and HCT-15) and for their inhibitory effects on nitric oxide production in lipopolysaccharide (LPS)-activated murine microglial cells.